Diagnosis and Management of Inherited Palmoplantar Keratodermas - Bjorn R. Thomas; Edel A. O'Toole (Medical Journals Sweden, 2020)
Inherited monogenic palmoplantar keratodermas are a heterogeneous group of conditions characterised by persistent epidermal thickening of the palmoplantar skin. Palmoplantar keratodermas are grouped depending on the morphology of the keratoderma into diffuse, focal/striate or papular/punctate. Some palmoplantar keratodermas just affect the skin of the palms and soles and others have associated syndromic features which include changes in hair, teeth, nails, hearing loss or cardiomyopathy. Next generation sequencing has helped discover genes involved in many of these conditions and has led to reclassification of some palmoplantar keratodermas. In this review, we discuss the diagnostic features of palmoplantar keratodermas and management options.